KEBERLANJUTAN PROGRAM DONASI E-WASTE PRODI TEKNIK INDUSTRI UNTAR DAN ECOSTAR GROUP SEBAGAI PRAKTIK MENDUKUNG SDG 4.7. DI KAMPUS - Kosasih, Wilson; Kristina, Helena Juliana; Simorangkir, Kenneth Pardamean; Wijaya, Chandra; Aprillita, Monica; Putri, Alifia Panny Kusuma; Jessica (Jurnal Bakti Masyarakat Indonesia, 2023)
The small to medium sized e-waste collection project within the scope of the UNTAR Industrial Engineering Study Program has been carried out since 2019 under the name EWASTE DONATION. Participants who donate e-waste are not only students and lecturers of the Industrial Engineering Study Program, Faculty of Engineering, UNTAR, but also the general public. However, due to the pandemic, this program has been hampered, so the community service team intends to revive this collaboration program. There is still a lack of knowledge of academics and the public regarding the function of the e-waste drop box in realizing a circular economy and supporting responsible recycling programs on campus. Therefore one of the tools that is considered the most appropriate for educating the academic community and the public about the existence of the e-waste donation program is through the creation of educational videos which are published on Youtube. The community service team in working on the video will use a linkage approach between SDGs and E-waste covering the 4 SDGs, with the following elaborations: a) The Dropbox e-waste program is part of TLI's innovation and infrastructure networking activities, the Ministry of Environment and Forestry, and the community will distribute electronic waste in a responsible and correct manner; b) Education on the importance of channeling e-waste to parties appointed by the Ministry of Environment and Forestry, in order to avoid environmental pollution due to electronic waste management activities which are still informal and also illegal; c) Responsible consumption because we realize that many materials in the production of electronic goods come from limited natural resources; d) The official e-waste dropbox network that is deployed will help create jobs and create a circular economy. The existence of the E-waste industry which is recognized by the Ministry of Environment and Forestry will also create jobs and economic growth, because good management of e-waste can create many new opportunities. ABSTRAK: Projek pengumpulan e-waste ukuran kecil sampai sedang di lingkup Prodi Teknik Industri UNTAR telah dilakukan sejak tahun 2019 dengan nama DONASI EWASTE. Partisipan yang mendonasikan e-waste bukan hanya dari mahasiswa dan dosen Prodi Teknik Industri, Fakultas Teknik, UNTAR, tetapi juga masyarakat umum. Tetapi karena pandemi, program ini terhambat, sehingga tim PKM bermaksud menghidupkan kembali program dropbox e-waste di Fakultas Teknik UNTAR ini. Masih minimnya pengetahuan sivitas akademika dan masyarakat mengenai fungsi drop-box e-waste dalam mewujudkan circular economy dan mendukung program daur ulang bertanggung jawab di kampus. Oleh karena itu, salah satu alat yang dianggap paling tepat untuk mengedukasi sivitas akademika dan masyarakat akan keberadaan program donasi e-waste yaitu melalui pembuatan video edukasi yang dipublikasi di Youtube. Tim PKM dalam menggarap video tersebut menggunakan pendekatan keterkaitan antara SDG dan e-waste mencakup 4 SDG, dengan elaborasi sebagai berikut: a) Program dropbox e-waste adalah bagian kegiatan inovasi dan jejaring infrastruktur TLI, KLHK, dan komunitas masyarakat akan penyaluran sampah elektronik secara bertanggung jawab dan benar; b) Pendidikan akan pentingnya menyalurkan e-waste ke pihak yang ditunjuk KLHK, demi menghindari pencemaran lingkungan karena aktivitas pengelola limbah elektronik yang masih bersifat informal dan juga illegal; c) Konsumsi yg bertanggung jawab karena menyadari banyak material dalam produksi barang elektronik yang berasal dari sumber daya alam yang terbatas jumlahnya; d) Jejaring dropbox e-waste resmi yang disebar akan membantu membuka lapangan pekerjaan dan mewujudkan sirkuler ekonomi. Keberadaan industri e-waste yang diakui KLHK juga akan membuka lapangan kerja dan pertumbuhan ekonomi, karena pengelolaan e-waste yang baik dapat menciptakan banyak peluang – peluang baru.